Answer :

Answer:

[tex] (x_1 =2, y_1 = 6), (x_2 = 2, y_2 = 4)[/tex]

[tex] m =\frac{y_2 -y_1}{x_2 -x_1}[/tex]

And replacing we got:

[tex] m=\frac{4-6}{8-3}= -\frac{2}{5}[/tex]

And for this case we can use the first point to find the intercept like this:

[tex] 6 = -\frac{2}{5}(3) +b[/tex]

And solving we got:

[tex] b = 6 +\frac{6}{5}= \frac{36}{5}[/tex]

And then the line equation would be given by:

[tex] y = -\frac{2}{5}x +\frac{36}{5}[/tex]

Step-by-step explanation:

For this case we have the following two points given:

[tex] (x_1 =2, y_1 = 6), (x_2 = 2, y_2 = 4)[/tex]

And for this case we want an equation for a line with the two points given by:

[tex] y = mx+b[/tex]

Wher m is the slope and b the y intercept. We can find the slope with this formula:

[tex] m =\frac{y_2 -y_1}{x_2 -x_1}[/tex]

And replacing we got:

[tex] m=\frac{4-6}{8-3}= -\frac{2}{5}[/tex]

And for this case we can use the first point to find the intercept like this:

[tex] 6 = -\frac{2}{5}(3) +b[/tex]

And solving we got:

[tex] b = 6 +\frac{6}{5}= \frac{36}{5}[/tex]

And then the line equation would be given by:

[tex] y = -\frac{2}{5}x +\frac{36}{5}[/tex]

Other Questions